An empirical study in building brand loyalty in wardah cosmetics - Dedeh Kurniasih; Didit Haryadi; Wahyudi Wahyudi (Institute of Computer Science (IOCS), 2023)
The value of products to get products from the money they spend to get benefits on the brand of a product or service, after that having a lifestyle that is more than the beginning. This raises the right for customers to be able to sort out the best product or service brands, which creates automatic customer happiness by indirectly demanding that companies must be able to create a stronger brand more than just ordinary products or services. The purpose of this study is to explore the factors that can increase loyalty to the Wardah Cosmetic brand. This study was conducted on Primagraha University students, especially in management study programs with a population of 403, while those drawn into the sample were 130 with a purposive sampling technique. The method used in this research is an associative quantitative approach with a survey method, the data analysis technique used in this research the author uses SmartPLS. The results showed that brand loyalty is influenced by brand experience, brand loyalty is influenced by brand trust, and brand trust can moderate the relationship between brand experience and brand loyalty